Habitual physical activity in patients born with oesophageal atresia: a multicenter cross-sectional study and comparison to a healthy reference cohort matched for gender and age - König, Tatjana T.; Frankenbach, Maria-Luisa; Gianicolo, Emilio; Holler, Anne-Sophie; von Sochaczewski, Christina Oetzmann; Wessel, Lucas; Widenmann, Anke; Klos, Leon; Kolb, Simon; Siaplaouras, Jannos; Niessner, Claudia (European journal of pediatrics, 2023)
Oesophageal atresia (EA) is associated with life-long gastrointestinal and respiratory morbidity and other associated malformations. The aim of this study is to compare physical activity (PA) levels of children and adolescents with and without EA. A validated questionnaire (MoMo-PAQ) was used to evaluate PA in EA patients EA (4-17 years), who were randomly matched for gender and age (1:5) with a representative sample of the Motorik-Modul Longitudinal Study (n = 6233). Sports activity per week (sports index) and minutes of moderate to vigorous physical activity per week (MVPA minutes) were calculated. Correlations between PA and medical factors were analysed. In total, 104 patients and 520 controls were included. Children with EA were significantly less active at higher intensities (mean MPVA minutes 462; 95% confidence interval (CI): 370-554) compared to controls (626; 95% CI: 576-676), although there was no statistically significant difference in the sports index (187; 95% CI: 156-220 versus 220; 95% CI: 203-237). A lower mean weight-for-age and height-for-age, additional urogenital (r =  − 0.20, p = 0.04) or anorectal malformation (r =  − 0.24, p = 0.01) were associated with fewer MVPA minutes. For other medical factors (prematurity, type of repair, congenital heart disease, skeletal malformation or symptom load), no statistically significant association with PA was found.